Familial Congenital Aniridia with Subluxated Lens and Glaucoma - Perwitasari, Birgitta Henny; Hermawan, Dicky (Universitas Airlangga, 2023)
Introduction: Congenital aniridia is a bilateral iris aplasia or hypoplasia associated with other ocular disorders. The purpose of this case report is to describe the clinical manifestation of congenital aniridia in two members of one family. Case Presentation: The first patient (mother) is a 43-year-old and the second patient (daughter) is a 12-year-old. Both patients complained of blurred vision since childhood. The visual acuity of the first patient was a positive light perception on the right eye (RE) and no light perception on the left eye (LE); the visual acuity of the second patient was 1/60 on the RE and 3/32 on the LE. Both patients had horizontal nystagmus and increased intraocular pressure (IOP) (N+1 palpation) in both eyes. Anterior segment abnormalities of both patients include aniridia with iris rudimentary and superiorly subluxated lens. The first patient also had LE corneal leukoma and RE cataract. The second patient also had right and left eye corneal conjunctivalization. Fundus examination showed no fundus reflex on the first patient and tigroid retina with foveal hypoplasia on the second patient. Eye ultrasounds of both patients showed vitreous opacity. Conclusions: Congenital aniridia primarily originates from a mutation in the paired box gene-6 (PAX6) and is associated with other ocular anomalies such as nystagmus, amblyopia, keratopathies, cataract, lens luxation, glaucoma, fovea, optic nerve hypoplasia. Patients in this case showed similar conditions between mother and daughter, however, the mother's condition was more advanced and more degenerated than the daughter's condition.